2018
DOI: 10.1111/dom.13400
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the SGLT2 inhibitor luseogliflozin on pancreatic β‐cells in db/db mice: The earlier and longer, the better

Abstract: Luseogliflozin exerts more protective effects in an early stage of diabetes compared to an advanced stage, and longer-term use of luseogliflozin exerts more beneficial effects on pancreatic β-cells compared to short-term use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 66 publications
1
45
1
Order By: Relevance
“…In the current study, food intake of group db/db(c+) was greater than that of group db/db(c−), and decreased insulin secretion in group db/db(c−) and preserved insulin secretion in group db/db(c+) were shown by weekly blood collection or OGTT. These results are comparable with previous reports 26,27 .…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, food intake of group db/db(c+) was greater than that of group db/db(c−), and decreased insulin secretion in group db/db(c−) and preserved insulin secretion in group db/db(c+) were shown by weekly blood collection or OGTT. These results are comparable with previous reports 26,27 .…”
Section: Discussionsupporting
confidence: 93%
“…Owing to increased cell proliferation and decreased β-cell apoptosis, a larger pancreatic β-cell mass was observed in mice treated with luseogliflozin. Additionally, the β-cellrelated factors were significantly increased in the luseogliflozintreated mice, and the insulin gene transcription factors, MafA and PDX1, and insulin levels were increased (62). In empagliflozin-treated mice, the expression levels of βcell-related factors, including insulin, MafA, PDX1, GLP-1 receptor, and glucose transporter Glut2, were increased.…”
Section: Sglt2 Inhibitors Promote the Expression Of Different β-Cell-mentioning
confidence: 95%
“…We speculated that relief from glucotoxicity by LC and SGLT2i could indirectly support to prevent beta-cell death and alpha-cell expansion in part. Some previous reports indicated that beta-cell mass was sustained by treatment with either SGLT2i alone or SGLT2i plus insulin, but not by insulin alone in diabetic rodent models (25)(26)(27). Thus, we speculate that SGLT2i per se might directly protect islet morphology.…”
Section: Discussionmentioning
confidence: 57%